Counter Application Trainer for Teaching Aids in Digital Electronic Course - Madar, Ahmad Rizal; Sumarwati, Sri; Hamid, Hashima; Amiruddin, Mohd Hasril; Musa, Nor Athirah (Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
Teaching aids play a vital role in the teaching and learning process. Teaching aids are crucial in helping students comprehend learning theory. However, most existing counter application trainers as teaching aids in digital electronics courses are developed without following the syllabus in vocational colleges and come at a high price. This study aimed to develop a counter application as teaching aids in digital electronics courses to provide low-cost teaching aids tailored to the curriculum at vocational colleges. This quantitative research applied the Life Development System (SDLC) model. This study developed a counter application trainer for teaching the Electronic and Digital Application course in vocational colleges. The findings showed that the product has been validated by experts based on the product design, suitability, and functionality. Further investigation could be conducted by looking into the trainer’s safety features, such as adding a cap to the transformer’s supply circuit and the on/off switch. Electric shock can be avoided with this cover.